M-Learning in Croatia: Mobile Multimedia Systems for Distance Learning - Vuksanović, Irena (Array, 2007)
Education and following processes, knowledge market and competition, are for long recognized on global level. Information communication technology fast growth and new generations great computer knowledge enables new teaching methods development. Until fifteen years ago focus was on computer who used primary CD and local networks as information media, and then it spread on Internet usage and numerous possibilities which enables distance learning (e-Learning), and in that context special accent is put today's on mobile learning (m-Learning) perspective and its usage possibilities.